The role of sponsor and external management on the capital structure of Asian-Pacific REITs: The case of Australia, Japan, and Singapore - Dong Chen; Yanmin Gao; Mayank Kaul; Charles Ka Yui Leung; Desmond Tsang (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This paper studies how the presence of sponsor and external management affect leverage and debt maturity decisions in three major Asian-Pacific REIT markets: Australia, Japan and Singapore. Our empirical results indicate that sponsored REITs opt for higher levels of leverage and loans with longer maturity. On the contrary, externally managed REITs are associated with lower leverage and loans with shorter maturity. Our results are robust to the inclusion of other firm variables and to alternative specifications. Subsequent to the financial crisis, the impact of sponsorship on debt financing decisions has diminished, and borrowing of externally managed REITs is further constrained.
Keywords: F30; G10; R30; 330; Asian-Pacific REIT markets; capital structure; debt maturity; simultaneous equation modelling; financial crisis